2022
DOI: 10.1111/opec.12228
|View full text |Cite
|
Sign up to set email alerts
|

A nexus between renewable energy, FDI, oil prices, oil rent and CO2 emission: panel data evidence from G7 economies

Abstract: Volatile energy prices, supply chain vulnerability and ecological implications of depleting fossil fuels have obligated the nations to swap carbon energy resources with sustainable and consumption energy choices. The study aims to investigate the sustaining connection of renewable energy consumption with trade openness, oil rent (OR), oil prices (OP) and carbon dioxide emissions of the G7 nations over the period 1971-2019. Using FMOLS and DOLS approach to panel data for analysing the long-run elasticity, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…With the constant change of the weighting coefficient, the convergence speed of improved PSO-PFCM iterative calculation is continuously improved, and the global search capability is greatly increased. In order to ensure that the inertial weight of carbon emission data outflow in each iteration calculation can be balanced and adjusted [8]. Introduce the test function…”
Section: Carbon Emission Efficiency Overflow Detection Based On Impro...mentioning
confidence: 99%
“…With the constant change of the weighting coefficient, the convergence speed of improved PSO-PFCM iterative calculation is continuously improved, and the global search capability is greatly increased. In order to ensure that the inertial weight of carbon emission data outflow in each iteration calculation can be balanced and adjusted [8]. Introduce the test function…”
Section: Carbon Emission Efficiency Overflow Detection Based On Impro...mentioning
confidence: 99%
“…For example, (Ali et al 2022 The second trend (Figure 3b) analyzes the interlinkages between oil prices and CO 2 emissions. For example, (Ali et al 2022;Alkathery and Chaudhuri 2021;Apergis and Payne 2015;Royal et al 2022;Sadorsky 2009;Zaghdoudi 2017) analyze the co-movements among oil prices, CO 2 emissions, and renewable energy. The findings suggest that renewable energy improves environmental quality in both the short and long run; an increase in oil prices causes a decrease in CO 2 emissions and has an important effect on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, decreasing OR lowered CO 2 emissions in four countries. Royal, Singh & Chander (2022) investigated G7 countries from 1971–2019 employing Fully Modified Ordinary Least Square (FMOLS) and found that oil prices and rents increased REC in the panel. However, FDI could not encourage REC.…”
Section: Literature Reviewmentioning
confidence: 99%